PELATIHAN PEMBUATAN SABUN CUCI PIRING DI DESA WAY KANDIS KECAMATAN TANJUNG SENANG - Dewi, Novian Riskiana; Rahmadina, Nova; Ambarwati, Riyama (Fakultas Sains dan Teknologi, 2024)
Soap is an essential ingredient used to wash kitchen utensils, clothes, household furniture, the body, and so on. Soap is made from a mixture of alkali and triglycerides from fat. Dish washing soap is a necessity in the household which functions as a remover of dirt and grease on eating and cooking utensils. This article contains information and explanation regarding the work program for making dishwashing soap. The complete description of this article includes the provision of materials, processes or manufacturing steps to the results and implementation of the results to the community. The approach used is qualitative-descriptive. The output from carrying out this activity is increasing the capability of Ummahat women in Way Kandis Village in making economically valuable dishwashing soap. Keywords: Soap, Dish Soap, Training